A distributed push-based XML access control model for better scalability - Halboob, Waleed Abduljabbar Mohammed; Mamat, Ali; Mahmod, Ramlan (IEEE, 2008)
XML access control is a non-trivial topic as XML language becomes a standard for data representation and transmission on the Web. Existing access control approaches to the published XML documents are not likely to scale well since they specify and enforce their access control policies in centralized servers. This paper proposed a distributed model for providing a scalable access control to the published XML documents. The proposed model is cost-effectively distributed for meeting the increased workload along with avoiding the possible bottlenecks. As a result, the proposed model effectively scales with the increased system and management workloads.